Traffic Light Berbasis Logika Fuzzy pada Kasus Persimpangan Dalam Kota dengan Satu Jalur Kepadatan yang Dinamik - Ujianto, Septrian (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
The purpose of this research is designing a traffic light control system based on fuzzy logic on intersection with one lane that have dynamic density models in MATLAB and comparing averaged waiting time between fuzzy logic method, adaptive method, webster method and automated density method. The method used in this research is fuzzy logic method with inputs in the form of congestion sensor and real-time clock and also output in the form of duration of green light of each roads. The result of averaged waiting time in this system based on fuzzy logic method, adaptive method, webster method and automated density are 3,13647 s; 3,3 s; 6,43 s and 3,72 s respectively. Based on the result of the experiment, we can conclude that a traffic light control based on fuzzy logic have a lower averaged waiting time when compared to other methods with condition 1, 3, 6 and 7 have a lower waiting time because the duration in that condition is much lower than other conditions.